Integrating Design Thinking into Entrepreneurship Education: A Learning Framework for Vocational High School Students - Maman Achdiat; Hawa Liberna; Nur Rizkiyah; Husain Nurisman; Sigit Widiyarto; Hugo Aries Suprapto; Dellia Mila Vernia; Saring Saring (AL-ISHLAH: Jurnal Pendidikan, 2025)
Entrepreneurship education requires dynamic and contemporary learning methods. Design thinking is a promising approach to fostering independence, innovation, and problem-solving skills among students. This study aims to evaluate the effectiveness of the design thinking method in entrepreneurship learning and to analyze its implementation process in vocational high schools. This research employed an experimental design using a pretest-posttest model within the same class. A total of 41 vocational high school students participated as the study sample. Data were analyzed using paired sample t-tests in SPSS 26 to assess the impact of the intervention on students’ entrepreneurial competencies. Findings indicate that the design thinking method is moderately effective in enhancing students’ entrepreneurial skills. The learning process is conducted both inside and outside the classroom, fostering an experiential learning environment. Students demonstrate improved innovation and critical thinking skills, particularly in identifying and addressing problems based on customer feedback. The study highlights the potential of design thinking as an effective pedagogical approach for entrepreneurship education in vocational schools. By engaging students in real-world problem-solving, this method enhances their adaptability and responsiveness to market needs. Future research could explore its long-term impact and applicability in different educational settings.